When substances in solution are dealt with, Thomsen indicates their state by affixing Aq to their symbols.
Thus [NaOH Aq, HNO 3 Aq] =13680 cal.
Thus the equation Cl 2 -1-2KI, Aq=2KC1, Aq+12+52400 cal., or (C12) +2KI, Aq =2KC1, Aq+-I-52400 cal., would express that when gaseous chlorine acts on a solution of potassium iodide, with separation of solid iodine, 52400 calories are evolved.
When C vanishes j has the form j = pxg x, and (f,j) 3 = (ap) 2 (aq)ax = o.
Hence, from the identity ax (pq) = px (aq) -qx (ap), we obtain (pet' = (aq) 5px - 5 (ap) (aq) 4 pxg x - (ap) 5 gi, the required canonical form.
Then, if Q be any radiant point and Q' its image (primary focus) in the spherical mirror AP, we have 1 1 2cos4) v l + u 'a ' ' where v 1 = AQ', u =AQ, a =OA, =angle of incidence QAO, equal to the angle of reflection Q'AO.
A similar expression can be found for Q'P - Q"A; and thus, if Q' A =v, Q' AO = where v =a cos (0", we get - - -AQ' = a sin w (sin 4 -sink") - - 8a sin 4 w(sin cktan 4 + sin 'tan cl)').
The grating at A and the eye-piece at 0 are rigidly attached to a bar AO, whose ends rest on carriages, moving on rails OQ, AQ at right angles to each other.
A =p n, b= aq, c- 2n bq, and so on.
From equations (i), we find that aq _ o a pi qi -, so that the extension of the new range is seen to be dp i dq i ...
So far as is known, each line in the spectrum of, say, mercury, represents a possibility of a distinct vibration of the mercury atom, and accordingly provides two terms (say aq;, 2 +.
The generalized formula is fxo u¢ (x)dx = Aq(xm) - where 0, A 2, ...
If we suppose alb to be converted into a continued fraction and p/q to be the penultimate convergent, we have aq-bp= +1 or -1, according as the number of convergents is even or odd, which we can take them to be as we please.
Let APB be a semicircle, BT the tangent at B, and APT a line cutting the circle in and BT at T; take a point Q on AT so that AQ always equals PT; then the locus of Q is the cissoid.
If we take aq-bp= +1 we have a general solution in integers of ax+by=c, viz.
X = cq - bt, y = at -cp; if we take aq-bp= - I, we have x=bt-cq, y=cp-at.